Analisis Kebutuhan Materi Ajar “Berbicara Bahasa Arab” Berbasis Pendekatan Komunikatif bagi Pembelajar Non-Bahasa Arab - Achmad Syarifuddin (Intizar, 2017)
Speaking is very synonymous with a person's ability to use the language in communication. Therefore, to have Arabic skill means that ability to use the Arabic language in speaking. Not just to say "Arab" that everyone can do it. But, however, speaking is often considered as a big problem, so it is not uncommon to target this ability is avoided because it is considered difficult. In addition, for Indonesian people, especially who do not or rarely interact with people who speak Arabic in their daily life, speaking Arabic is is bored thing and it does not become a necessity. In fact, every human being is given a gift by God in the form of the ability to speak. Even in terms of mantiq science, human is referred to as "al-hayawan al-natiq" (human being is a living being who speaks). This study analyzed the need to speak Arabic as a foreign language in the State Islamic College (PTKIN) includes needs category, learning method in Communicative approach. From the result of the research, it can be concluded that the non-linguistic department students in PTKIN (especially UIN Raden Fatah Palembang) are included in the category of beginner in learning Arabic, while the Arabic learning requirement category is included in the category of normative needs. However, with a communicative approach the Arabic learner can achieve speaking skills in the form of short conversations and introducing himself.